Differential media effects on male body satisfaction and mood. (6th August 2019) - Allen, Andrew; Mulgrew, Kate E.
Abstract: Objective: Previous research has shown that idealised images of men in the media have the capacity to trigger body dissatisfaction in male viewers. However, little is known about these effects across diverse media types. This study compared the effects of different media on men's body satisfaction and mood within a social comparison theory framework. Method: Young adult men ( N = 110) were randomly assigned to view images of scenery or idealised depictions of males across four media conditions including television commercials, music video clips, still images where the model was posed, or still images where the model was active. Men completed pre‐ and post‐test measures of state body satisfaction and mood, and a post‐test measure of social comparison. Results: Men who viewed television commercials reported a significant drop in body satisfaction and greater social comparison. No effects were found across the other media types. Conclusion: Our findings suggest that televised depictions may be particularly detrimental to men's body image, which may be due to increased social comparison processes.